Arabic Language Learning Technology in the First Cycle of Basic Education/تكنولوجيا تعلّم اللغة العربية في الحلقة الأولى من التعليم الأساس - Kurniadi, Fakhar (JURNAL IJ-ATL, 2017)
The educational media and technologies are: materials and tools that are partially or wholly employed in school education to create learning. The school, the teacher, the spoken word, the book, the picture, the slide, the film, the computer, the expert, etc., Educational tools and technology are important to guide students' formal education and production. Education technology is a practical method of thought, with an integrated base of actors. Educational means are part of educational techniques or educational technology. Educators say: "Give the learner something to do better than give him something to learn." It is an innovative shift that gives the educational process new patterns of movement and interaction, and educational technology has become an important part of the teaching and learning process. The technology of education is a process that is not limited to the use of modern machines and devices, but mainly means the method of thinking, to develop a system-approach, that is to say a method, model, and method of work, follow the steps of organization, All technology, according to modern teaching and learning theories.إن وسائل التعليم (Educational Media And Technologies) هي: مواد وأدوات، توظّف جزئياً، أو كلياً، في التربية المدرسية، لإحداث عملية التعلّم، فالمدرسة والمعلم، والكلمة الملفوظة، والكتاب، والصورة، والشريحة، والفيلم، والحاسوب، والخبير وغيرها، تعدّ وسائل وتكنولوجيا تعليميّة مهمة، لتوجيه التربية الرسميّة للتلاميذ وإنتاجها. فتكنولوجيا التعليم هي طريقة فكرية عملية، لها قاعدة متكاملة من العناصر الفاعلة، والوسائل التعليمية جزء من التقنيات التعليمية، أو تكنولوجيا التعليم إذ يقول التربويون: (أعطِ المتعلّم شيئاً يفعله أفضل من أن تعطيه شيئاً يتعلّمه). إنها نقلة مبتكرة تضفي على العملية التعليميّة أنماطاً جديدة من الحركة والتفاعل، وأصبح للوسائل التقنيّة التعليميّة دور مهم في عملية التعليم والتعلّم. وتكنولوجيا التعليم فهي عملية لا تقتصر دلالتها على مجرد استخدام الآلات، والأجهزة الحديثة، و لكنها تعني أساساً منهجية التفكير، لوضع منظومة تعليمية (System-approach)، أي اتباع منهج، وأسلوب، وطريقة في العمل، تسير على وفق خطوات منظّمة، مستعملة الإمكانات التي تقدمها التكنولوجيا كافة، على وفق نظريات التعليم والتعلّم الحديثة.